The women development fund and women empowerment in Zimbabwe: a case of Chipinge district ward 6 and 17 - Chikanyambidze, Getrude (Midlands State University, 2017)
In many African countries, women are marginalised in terms of their access to capital means of production, employment opportunities as well as credit facilities. In Zimbabwe, like many African countries empowering women through enlarging their access to finance has been viewed as a means of reducing women’s abject poverty, empowering them through reducing their vulnerability and improving their welfare. This study sought to find out if the government initiative Women Development Fund (WDF) has contributed to women empowerment. The study was carried out in ward 6 and 17 of Chipinge district in Manicaland province. To acquire relevant data, the study employed stratified random sampling and purposive sampling and data was collected using questionnaires and interviews. The study was guided by the Women Empowerment Framework postulated by Sara Longwe. Research revealed that WDF as a tool for women empowerment has made a contribution in improving the livelihoods of the beneficiaries through initiation of income generating projects which as a result led to economic, social, political, psychological and legal empowerment of women. However, the major handicap with WDF is that the amount of money given is not sufficient, the fund took long time to be disbursed and that it is implemented in isolate hence there is the need have complementary initiatives which encompass capacity building so as to enhance entrepreneurship skills of the beneficiaries, creation of market linkages among others.